Genetic and Epigenetic Associations with NAFLD: Focus on Clinical Decision Making and Novel Concepts in Disease Pathogenesis - Sookoian, Silvia Cristina (2014)
Nonalcoholic fatty liver disease (NAFLD) is a complex liver disease with worldwide prevalence. Its development involves a myriad of factors, including genetic susceptibility and environmental insults. In this review, we summarize new findings about current genome-wide association studies on NAFLD. In addition, we used a strategy of functional enrichment analysis to integrate all the newly discovered loci into common biological pathways and to explore their role in the pathogenesis of NAFLD. Controversies on the application of genetic testing to predict disease severity are discussed and specifically the role of rs738409 in clinical decision making. Finally, we highlighted significant trends and developments in epigenetic changes and microRNAs associated with disease progression.